Pengaruh Computer Anxiety Terhadap Keahlian Karyawan Dalam Menggunakan Komputer - Handoyo, Sigit; Cahyono, Nike Ardhini (Optimum: Jurnal Ekonomi dan Pembangunan, 2011)
This study entitled "The Effect of Computer Anxiety alongside Employees in Using Computer Skills" aims of the study is to examination significant result between computer anxiety and computing skill. The number of 97 respondent employees as sample who working in the Universitas Islam Indonesia. Data collection techniques using questionaires and measured using a Likert scale of measurement. The analysis tools are simple regresion test. The result of this study shows that computer anxiety strong significantly toward using computers skills level employee